Drying of carrot pomace and utilization in the bread for improving nutrition values - ศุภมิตรโยธิน, ปรรัตน์ (KKU Science Journal, 2018)
Vegetable by-product are considered as a good source of dietary fiber and other biologically important compounds. Especially, by product of carrot after juice extraction represent promising sources of beta-carotene, phenolic and fiber that could be explored in the development of food ingredients and dietary supplement. The objective of this study was to determine the drying method and condition of carrot pomace by sun drying and tray drying at 50 and 60 ºC. The effects of carrot pomace powder levels on the quality and sensory characteristic of the bread were also investigated. Optimal drying was observed at 50 ºC for 240 min as it provided the dried product with high fiber (18.51 %) and protein (8.25 %)content as well as low fat (1.12 %)content. The best bread product from physical properties and sensory evaluation point of view was 5% addition of carrot pomace. The results show that bread supplement with carrot pomace not only increases nutrition value of products but also have significance on the quality and sensory acceptability of the bread.